Reimagining university–community engagement - Vally, S. (South African Journal of Higher Education, 2023)
This article is based on a keynote address to the second Higher Education Conference in the wake of the Covid-19 pandemic and the environmental and inequality crises confronting South Africa and the world. After an examination of the societal context of universities, the article discusses critical issues in relation to university-community engagement. It attempts to address these issues by firstly providing an overview of the long-standing debates in our country concerning the academy’s responsibilities and accountability to various constituencies beyond the universities gates and the imperative to rethink scholarship to engage communities meaningfully. Secondly, it will provide an appreciation of the overarching political economy of higher education and the corporatisation of universities before drawing conclusions about the processes that impede or allow the university to be responsive to community engagement. The article will provide a few historical and contemporaneous examples of the work of university-based researchers with various communities. The research of those who have an orientation toward working class communities and aim to democratise knowledge production will be highlighted. It will be argued that the latter’s “praxis epistemology” (Amini 2017) assists us in reimagining university-community relations.